Factors affecting the stability of the spike-triggered averaged force in the human first dorsal interosseus muscle - Gossen, E.Roderich; Ivanova, Tanya D; Garland, S.Jayne (Journal of neuroscience methods, 2003)
The reproducibility of motor unit twitches obtained using spike-triggered averaging (STA) was examined in the human first dorsal interosseus. For each motor unit (30 total) a series of STA twitches was derived using a 30 s averaging window. Within each averaging window, eight independent measures characterizing motor unit discharge and whole muscle force properties were recorded. These included the mean and standard deviation (S.D.) of the interspike interval (ISI), the mean and S.D. of pre and post-trigger ISIs used in averaging, and mean and S.D. of whole muscle force. To determine the relative importance of the independent variables on twitch reproducibility, the variables were used in a multiple regression analysis performed on STA twitch peak force (PF), time to peak force (TTP) and time of half-force decay (HFD). It was found that PF was significantly correlated to the mean and S.D. of whole muscle force, and mean post-trigger ISI. TTP was significantly correlated to the S.D. of the post-trigger ISI and mean whole muscle force while HFD was related to the mean and S.D. of the pre-trigger ISI and the mean post-trigger ISI. It was concluded that by minimizing whole muscle force variability and the mean and S.D. of acceptable ISIs used in the STA process, the reproducibility of the STA twitch is improved.